A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species - Schmid-Egger, Christian; Fallahzadeh, Majid; Sadeghi, Maryam (Zootaxa, 2021)
Species of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) in Iran are revised and a key to species is given. The following species from southern Iran are described, based on females only: Solierella farsica Schmid-Egger sp. nov., Solierella kermania Schmid-Egger sp. nov., Solierella khafriensis Schmid-Egger sp. nov. and Solierella persica Schmid-Egger sp. nov. In addition, four species, S. insidiosa de Beaumont, 1964, S. pisonoides (Saunders 1873), S. syriaca de Beaumont, 1964 and S. verhoeffi de Beaumont, 1964 are recorded for the first time for fauna of Iran. Solierella compedita (Piccioli, 1869) could not be confirmed for the fauna of Iran, recognition characters of S. insidiosa and S. compedita are discussed. The number of Solierella species in Iran raises to ten.